2009
DOI: 10.1007/s00428-009-0850-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive cytokine Interleukin-10 (IL-10) is up-regulated in high-grade CIN but not associated with high-risk human papillomavirus (HPV) at baseline, outcomes of HR-HPV infections or incident CIN in the LAMS cohort

Abstract: Bypassing the local immunological defense reactions in the cervix is one of the prerequisites for human papillomaviruses (HPV) infections to progress to intraepithelial neoplasia (CIN). The role of potent immunosuppressive cytokines, e.g., interleukin-10 (IL-10), depressing these local virus-specific immunological responses is incompletely studied. To assess, whether IL-10 expression in cervical HPV lesions has any implications in the outcome of HPV infections or disease progression to CIN. Baseline cervical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
(116 reference statements)
0
20
0
3
Order By: Relevance
“…A link has been shown between IL-10 expression and HPV-infected CIN progression [35]. Therefore, we expected to find differential IL-10 mRNA expression levels between HPV-positive and -negative OSCC.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A link has been shown between IL-10 expression and HPV-infected CIN progression [35]. Therefore, we expected to find differential IL-10 mRNA expression levels between HPV-positive and -negative OSCC.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, IL-10 has been documented to determine in vivo virus clearance or persistent infection. Previously, IL-10 expression levels were reported as significantly higher in an HPV16-infected high grade of cervical intraepithelial neoplasia (CIN) II and III when compared to normal cervical epithelium and CIN I [33][35]. This suggests that IL-10 production may play a role in the progression of HPV-associated cervical precancer [34].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of IL-10 in cervical lesions was most commonly upregulated in high-grade CIN. This immunosuppressive cytokine may play an important role in creating a microenvironment that favors progressive cervical disease and immune evasion by high-risk HPV (31) and may also explain the immunosuppressive state of cervical cancer patients (32). Women who are genetically programmed to produce high or moderate levels of IL-10 are more likely to develop cancer of the uterine cervix, compared to individuals genetically predisposed to low IL-10 production, suggesting that the genetically acquired ability to produce higher levels of IL-10 may be a significant factor in the development of cervical cancer (17).…”
Section: Il-10 Exerts a Tumor-promoting Effect In Cervical Cancermentioning
confidence: 99%
“…In women with HPV16-positive CIN, El-Sherif et al observed decreased levels of IFNÁ and TGFß mRNA and increases of IL-10 compared to healthy HPV-negative controls (36,37). Others recently found that elevations in IFNÁ and IL-10 were associated with decreased odds of having CIN 2 or 3 (38,39). Using immunohistochemistry, Behbahani et al located more IL-2 and IL-4 expressing cells as signs of immune activation in HPV-positive women compared to negative controls (22).…”
Section: Discussionmentioning
confidence: 99%